Efficacy of Ricinus communis L., Cassia occidentalis L. and Bacillus thuringiensis against Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) - Elamin Elhaj, Waleed; Ahmed Osman, Abdelgadir; Mohamed Elamin Elawad, Loai (Journal of Agronomy Research, 2021)
Helicoverpaarmigera is one of the most destructive pests of field crops worldwide. The Study was designed to investigate through laboratory screening the insecticidal activity of Ricinus communis, Cassia occidentalis and Bacillus thuringiensis var. Kurstaki (Btk) and their combinations against 2nd larval instar of H. armigera. Five concentrations (4%, 6%, 8%, 10% and 12%) of each plant extract and (0.62, 1.25, 2.5, 5, and 10 mg/ml) of Bt were used in this experiment. Mortality (%) was recorded after 24,48,72 and 96 hrs post treatment. The results showed that R. communis, C. occidentalis and Btkhave insecticidal activity against 2nd instar larvae of H. armigera. The highest concentration (12%) caused 80% and 70% larval mortality after 96 hrs for R. communis and C. occidental respectively. The statistical analysis revealed that there is a significant differences between all treatments and control. Additionally, all combinations (plant/plant or plant/Bt) increased the mortality %. The results also clearly demonstrate that the R. communis are significantly more toxic than C. occidental where the LC50 values were 6.4 % for R. communis and 8.1% for C. occidental. On the other hand LC50 value for Bt was 0.41 mg/ml. The binary mixture of R. communis and C. occidental have a potentiation effect after 48 hrs. Regarding the mixture of Bt and plant extracts the results revealed that R. communis and Bt mixture induced a potentiation effect whereas C. occidental and Bt mixture induced a an additive effects.
Keywords: Helicoverpaarmigera; Ricinus communis; Cassia occidental; Bacillus thuringiensis; Joint Action